Distributed adaptive Huber regression - Luo, Jiyu; Sun, Qiang; Zhou, Wen-Xin (Computational statistics & data analysis, 2022)
Distributed data naturally arise in scenarios involving multiple sources of observations, each stored at a different location. Directly pooling all the data together is often prohibited due to limited bandwidth and storage, or due to privacy protocols. A new robust distributed algorithm is introduced for fitting linear regressions when data are subject to heavy-tailed and/or asymmetric errors with finite second moments. The algorithm only communicates gradient information at each iteration, and therefore is communication-efficient. To achieve the bias-robustness tradeoff, the key is a novel double-robustification approach that applies on both the local and global objective functions. Statistically, the resulting estimator achieves the centralized nonasymptotic error bound as if all the data were pooled together and came from a distribution with sub-Gaussian tails. Under a finite (2+δ)-th moment condition, a Berry-Esseen bound for the distributed estimator is established, based on which robust confidence intervals are constructed. In high dimensions, the proposed doubly-robustified loss function is complemented with ℓ1-penalization for fitting sparse linear models with distributed data. Numerical studies further confirm that compared with extant distributed methods, the proposed methods achieve near-optimal accuracy with low variability and better coverage with tighter confidence width.